A Protocol to Understand the Implementation and Experiences of an Online Community-Based Performance Arts Programme Through and Beyond the COVID-19 Pandemic, Brain Waves - Estevao, Carolina; Taylor, Elizabeth; Jarrett, Lucinda; Fort, Joseph; Murphy, Kevin; Woods, Anthony; Crane, Nikki; Fancourt, Daisy; Pariante, Carmine M.; Jones, Fiona (Frontiers in Rehabilitation Sciences, 2022)
Introduction: Individuals living with acquired brain injury experience numerous psychological, physical, and social challenges. Since the COVID-19 pandemic, many have experienced additional isolation, mental health issues and have had limited access to social and physical activities otherwise available in the community. Materials and Methods: Brain Waves is a 12-week online performance arts programme developed during the COVID-19 pandemic, for people with acquired brain injury (ABI). The research component of Brain Waves is a qualitative study, using Interpretative Phenomenological Analysis (IPA) and ethnographic methods (Observations and Interviews). The study will recruit two distinct populations: individuals living with acquired brain injury (including people who have experienced traumatic brain injury and stroke who are participating in the programme) and stakeholders (facilitators, involved in the delivery of Brain Waves). The aim is to gain an understanding of the implementation and experiences of creating and participating in an online community-based performance arts programme.